Understanding customer journey from the lenses of complexity theory. Issue 11 (10th September 2019) - Varnali, Kaan
ABSTRACT: The present article develops an argument that conceptualizing the customer journey as a complex system provides both a systematic portrayal of the complex and holistic nature of customer experience and an opportunity to serve as an integrative framework for differing definitions in the service literature. A comprehensive literature review reflecting the contemporary understanding of the concept of customer journey is presented. Theoretical and practical implications of adopting a complexity theory-based stance in customer experience research are discussed under five fundamental tenets of complexity theory.